Pengaruh Model Quantum Teaching dengan Menggunakan Media Papan Multifungsi terhadap Hasil Belajar Matematika Siswa Kelas V UPTD SD Negeri 122366 Pematangsiantar: The Influence of the Quantum Teaching Model Using Multifunction Board Media on the Mathematics Learning Outcomes of Class V Students of UPTD SD Negeri 122366 Pematangsiantar - Rifka Teresia Br Barus; Ayuning Zahra; Rama Yana Meylansari Sipayung3; Eka Resti Barus (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Mathematics is one of the most important subjects at various levels of education, starting from elementary school to higher education, so it needs serious attention because mathematics is the basis of other sciences. To address the above, innovations in mathematics learning have emerged so that learning becomes more effective. This learning innovation is by using the Quantum Teaching learning model. This study aims to see whether there is an effect of quantum teaching using multifunctional board media on the mathematics learning outcomes of fifth-grade students of UPTD SD Negeri 122366 Pematangsiantar. This research is a quantitative research type with a one-group pretest-posttest research design. This research was conducted at UPTD SD Negeri 122366 Pematangsiantar. The sampling technique chosen by the researcher is non-probability sampling. The sample in this study was all fifth-grade students of UPTD SD Negeri 122366 Pematangsiantar, totalling 17 students. Research data shows the application of quantum teaching using multifunctional board media on mathematics learning outcomes has a pretest value with an average of 64.41, while the posttest is 72. The analysis test used is the t-test value based on the research results, then obtained t_count = 28.080 with a sig. (2-tailed) level of 0.000 significant probability <0.05 t_count,> t_table = 28.080 with a significant level <0.05 t_count,> t_table = 28.080> 2.110 then Ho is rejected and Ha is accepted. There is an influence of the quantum teaching learning model with a multifunctional board on mathematics learning outcomes in grade V students at UPTD SDN 122366 Pematangsintar.